Are golf courses a source or sink of atmospheric CO2: A modelling approach - Bartlett, Mark D.; James, Iain T. (Professional Engineering Publishing, 2011)
Sports facilities have been shown to have a positive impact on local biodiversity, quality of life and the economy. Their impact on global carbon balances is less clearly understood. Increased concentrations of atmospheric CO2 have been linked with global climate change. Currently there is debate as to whether amenity turf is a net source or a net sink for atmospheric CO2. The turfgrass of a natural sports pitch will sequester carbon through photosynthesis, but there are numerous emission sources associated with the management of turf which release CO2 into the atmosphere. These include the engines used to power mechanised operations such as mowing and spraying, the application of agrochemicals, including fertilizers, and the disposal of waste. In order to determine if a real-world example of a sports facility was a source or sink of carbon a mechanistic mass balance model was developed. Analysis indicated that, the areas of the golf course that received the most management attention were a net source of carbon emissions. The magnitude of these releases was significantly different on an equal area basis (p<0.01). The net carbon budget for turfgrass areas across the whole golf course, accounting for the sequestration by the turfgrass was -44.1 g C m-2 y-1. The mature trees that formed an integral part of the landscape of the modelled course had a significant impact on the net carbon balance, resulting in overall net sequestration of -145.4 Mg C y-1 for the whole golf course, equivalent to -1.48 Mg C ha-1 y-1. The variability in the size, shape and vegetation composition of different golf courses has a considerable impact on their net carbon balance, and the resultant environmental impact of sports facilities must be assessed on an individual basis.